A Case Report of a Patient with Spontaneously Resolving Unruptured Uterine Artery Pseudoaneurysm after Surgery for Miscarriage during the Early Stages of Pregnancy Using Manual Vacuum Aspiration - Toshiyuki Kakinuma; Kaoru Kakinuma; Yoshimasa Kawarai; Tomoyuki Ohta; Michitaka Ohwada; Hirokazu Tanaka; Kaoru Yanagida (Wolters Kluwer Medknow Publications, 2022)
Uterine artery pseudoaneurysms are caused by damage to blood vessel walls from iatrogenic changes including cesarean section or cervical dilatation and uterine curettage. Manual vacuum aspiration (MVA) is becoming increasingly popular from the perspective of reducing the risk of endometrial injury. This is a case report of a 33-year-old primigravida female patient diagnosed with an unruptured uterine artery pseudoaneurysm that spontaneously resolved after surgery for miscarriage using MVA. The patient experienced a miscarriage at 10 weeks and 0 days of gestation and underwent surgery using MVA. Fourteen days after surgery, the patient was diagnosed with a uterine artery pseudoaneurysm by transvaginal ultrasound tomography and contrast computed tomography of the pelvic region. The patient received elective follow-up and was found to be completely thrombosed 2 months after surgery. MVA for miscarriage may cause uterine artery pseudoaneurysms. Elective therapy may be an option for unruptured uterine artery pseudoaneurysms.